Mitigation of Alexandrium tamiyavanichii using active fractions from ethanol extract of ornamental plant, Sansevieria trifasciata - Mohammad Noor, Normawaty; Mohd Suberi, Ima Amirah; Darnis, Deny Susanti; Mukai, Yukinori; Iqbal, Anwar; Adam, Aimimuliani (Zibeline International Publishers, 2020)
Blooms of toxic Alexandrium tamiyavnichii have been recorded in several parts of the world including Malaysia. This Harmful algal bloom (HAB) has led to human illness and loss to fishery industries. In order to control the bloom and minimize the effects, the growth of the species needs to be inhibited using a mitigation agent, preferably environment friendly agent. In this study, an ornamental plant, Sansevieria trifasciata will be used to inhibit the growth of A. tamiyavanichii. The plants were fractionated to obtain fractions (dichloromethane (DCM) and methanol) from ethanol fresh and dried plants extracts. Eight concentrations (0.001, 0.01, 0.1, 0.5, 1.0, 1.5, 2.0 and 2.5 mg/mL) of these fractions were tested on the algae for 24 hours and removal efficiencies (RE) were determined. Toxicity test was conducted on Artemia using 10, 50, 100 and 500 mg/mL concentrations of active fractions for 24 hours. Phytochemical compounds were detected using standard procedures. Results obtained showed that the growth of A. tamiyavanichii was inhibited by all concentration tested. Active fractions from DCM using both fresh and dried plants showed good results with more that 80% RE values at 5 mg/mL within 2.5 to 5 hours. During the experiments, DCM used did not change the pH of the culture medium compared to methanol fraction. For phytochemical screening tests, compounds detected in all fractions were alkaloids, tannins, glycosides, reducing sugars and terpenoids. These compounds might cause the inhibition of targeted algae, however further study is needed to determine the bioactivity and its specific effect on HAB species. To conclude, fractions of DCM from fresh and dried S. trifasciata have the potential in the mitigation of A. tamiyavanichii. This could help to minimize the impact of this species on human health and reduce the loss to fishery industries.